2014
DOI: 10.5424/sjar/2014122-4566
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of fatty acid profiles of fat in commercial Spanish suckling kids and lambs

Abstract: Fatty acid profiles are a major contributor to meat quality in small ruminants. Nevertheless, while fatty acid profiles from suckling lambs have been extensively studied they are virtually unknown in suckling kids. Fatty acid profiles of intramuscular and kidney knob fat depots of suckling kids were compared with fatty acid profiles of lambs with a quality label in the Spanish market. Forty suckling kids from Blanca Celtibérica (BC), Moncaína (Mo), Negra Serrana (NS) and Murciano Granadina (MG) breeds and 20 C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
1
2

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
2
3
1
2
Order By: Relevance
“…However, in the present study, PL and TI, which are both dairy breeds, had higher percentages of trans MUFAs and most of the C18:1 isomers but lower amounts of the total MUFAs than RE (meat) and GU (mixed purpose). It was reported that meat kids show a higher percentage of CLA than dairy kids [57]. In the current results, the most abundant C18:1 isomers were C18:1c9 and C18:1 t11, in agreement with Adeyemi et al [58].…”
Section: Meatsupporting
confidence: 92%
See 1 more Smart Citation
“…However, in the present study, PL and TI, which are both dairy breeds, had higher percentages of trans MUFAs and most of the C18:1 isomers but lower amounts of the total MUFAs than RE (meat) and GU (mixed purpose). It was reported that meat kids show a higher percentage of CLA than dairy kids [57]. In the current results, the most abundant C18:1 isomers were C18:1c9 and C18:1 t11, in agreement with Adeyemi et al [58].…”
Section: Meatsupporting
confidence: 92%
“…Although the effects of the ratio on human health are less consistent than expected [61], it is accepted that this ratio must be lower than four [62]. Current results for kid meat varied between 4.78 and 13.00, in agreement with those of other authors [57]. The intramuscular fat from dairy animals, such as PL and TI, had a more unfavorable n-6:n-3 ratio than other breeds [55].…”
Section: Meatsupporting
confidence: 79%
“…Nonetheless, the observed AI values are lower than those previously found in mucuna bean (0.26; Mthiyane et al, unpublished) and meat fats (0.5 -1.0) [75,76]. High AI values indicate greater atherogenicity risk [77].…”
Section: Resultscontrasting
confidence: 55%
“…Oleic, palmitic and stearic acids are the most abundant MUFA and SFA in the IMF of small ruminants (Horcada et al 2014;Camacho et al 2017). The FA composition of meat is more affected by slaughter weight than by sex or breed (Camacho et al 2017).…”
Section: Discussionmentioning
confidence: 99%